The Effect of Side Obstacles of Kuok Traditional Market Activities on The Performance of The West Sumatra-Riau Traffic Road - Firdaus, Zulfadli; Adeswastoto, Hanantatur; Islah, Mhd. (Journal of Engineering Science and Technology Management, 2024)
As a transportation infrastructure, roads are essentially an important element in realizing economic growth and achieving healthy and dynamic social stability. Therefore, the performance of road sections needs to be considered. Road section performance can be defined as the extent to which the road is able to carry out its function. A survey conducted on 4 different days showed the performance of road sections during peak hours with a traffic volume (V) in the direction of Bangkinang-Payakumbuh of 905 vehicles/hour and in the direction of Payakumbuh-Bangkinang of 840 vehicles/hour, so that the total traffic volume on the Pasar Kuok road section is 1683 vehicles/hour. The total traffic flow (Q) on the Pasar Kuok road section is 1589.9 smp/hour. The capacity (C) on the Pasar Kuok road section is 2523.53 smp/hour. The degree of saturation (DS) of the Pasar Kuok road section is 0.61 while the V/C ratio on the Pasar Kuok road section is 0.64. That the class of side obstacles on the Pasar Kuok road section is very high (VH). It is concluded that the Sumbar - Riau road section, precisely at the Kuok market, experiences a very high saturation point on market days, namely Tuesday due to the activities of the Kuok traditional market. Because of the many vehicles parked on the shoulder of the road, street vendors (PKL) on the roadside and many people passing by on the road.